Answer: Hello!
There are two bags:
you write: "the weight of bag B is 3 pounds more than twice the weight of both bags of potatoes is 27 pounds."
this has no sense, I think you want to write something like:
"The weight of bag B is 3 pounds more than the weight of bag A, and twice the weight of both bags of potatoes is 27 pounds.
If we define B as the wheight of bag B, and A as the wight of bag A; we know that:
B - A = 3lb
2( B + A) = 27lb
in the first equation we can isolate B as: B = 3lb + A, and then replace it in the second equation:
2(B+ A) =27lb
2( (3lb + A) + A) = 27lb
6lb + 3A = 27lb
3A = 27lb - 6lb = 21lb
A= 21lb/3 = 7lb
now we can replace it in the first equation and get:
B - A = 3lb
B - 7lb = 3lb
B = 3lb + 7lb = 10lb
Then Bag A weights 7lb and bag B weights 10lb.